Fiscal Capacity And Environmental Performance In Indonesian Provinces: Does The Flypaper Effect Stick To Green Outcomes - Hichmah Nadiah; Loggar Bhilawa (Universitas Riau Kepulauan, 2026)
This study examines whether regional fiscal capacity measured by Regional Original Income (PAD) and transfer funds influences environmental performance in Indonesian provinces. Using balanced panel data from 34 Indonesian provinces (2020-2023), we employ Fixed Effect Model (FEM) regression to control for unobserved regional heterogeneity. Environmental performance is measured by the Environmental Quality Index (IKLH). Control variables include GRDP per capita, capital expenditure ratio, and economic structure. Partially, neither PAD nor transfer funds show statistically significant individual effects on environmental performance (p>0.05). However, both variables jointly contribute to explaining environmental outcomes when considered with control variables (F-statistic significant at p